Evaluation of renal cortical echogenicity in healthy cats using anisotropic backscatter artifacts and echogenicity differences among internal organs - Gong-Yi Yan; Pin-Chen Liu; Ming-Jen Kang; Wen-Sheng Li; Yen-Huan Lee; Kuan-Sheng Chen (Veterinary Quarterly, 2023)
AbstractBackground Renal cortical anisotropic backscatter artifact (CABA) is a hyperechoic region of the renal poles where the insonation of sound beams is perpendicular to the renal tubules within the renal cortex.Aims To determine whether renal CABA can be observed in healthy cats and to compare the echogenicity of renal CABA with that of the spleen and liver.Material and methods Images of the spleen, liver, kidneys, and urinary bladder were acquired from 30 clinically healthy cats with renal CABA. Echogenicity differences among organs and echo scores within urine were recorded and analyzed. All ultrasound images were acquired using a 7.2–14-MHz linear transducer. Univariate logistic regression was used to assess the associations between the presence of renal CABA and various variables.Results The prevalence of the renal CABA was 86.7% (26/30) and 93.3% (28/30) according to different observers. The reproducibility of renal CABA is substantial to excellent. The renal CABA echogenicity was greater or equal to the spleen and greater than the hepatic echogenicity in 90.0% of cats (27/30). For comparison with the spleen and liver, there were three and six combinations of echogenicity differences using the CABA and non-CABA regions, respectively. The renal cortical echogenicity in the CABA region was higher than the liver in all subjects. Renal CABA was not associated with age, body weight, gender, body condition score, or lipid droplets in the urinary bladder.Conclusion Renal CABA was present in most healthy cats and could be used for echogenicity comparisons with the liver and spleen.